2017
DOI: 10.1590/s0100-736x2017000100006
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptides for diagnostics and therapy: a veterinary medicine point of view

Abstract: Empirical studies proved that C-peptides are performing numerous intrinsic biological roles, and serve as a marker for pancreatic performance analysis. Since the last decade, C-peptide assays for differential diagnosis in veterinary diabetic patients are becoming more available, but still only for a very limited number of species. Studies on C-peptide as a diagnostic tool, therapy for associated complications, or as replacement therapies for C-peptide deficiency still showed not to be a common practice in vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Work comparing the amino acid sequences of C-peptides obtained from the pancreas of various mammal taxonomic families found that while the sequences vary, several prominent features of the C-peptide structures are preserved (Peterson et al, 1972; see also Landreh et al, 2014, Wahren 2004). Moreover, C-peptide has been successfully measured in the blood of domestic animals (dog, cat, horse; reviewed by Rosenfield et al, 2017). Together, these findings provide a promising basis for uCP measurements in non-primate mammals and future studies should validate existing immunoassays.…”
Section: Feasibility Of Ucp As a Tool For Understanding And Mitigatin...mentioning
confidence: 91%
See 1 more Smart Citation
“…Work comparing the amino acid sequences of C-peptides obtained from the pancreas of various mammal taxonomic families found that while the sequences vary, several prominent features of the C-peptide structures are preserved (Peterson et al, 1972; see also Landreh et al, 2014, Wahren 2004). Moreover, C-peptide has been successfully measured in the blood of domestic animals (dog, cat, horse; reviewed by Rosenfield et al, 2017). Together, these findings provide a promising basis for uCP measurements in non-primate mammals and future studies should validate existing immunoassays.…”
Section: Feasibility Of Ucp As a Tool For Understanding And Mitigatin...mentioning
confidence: 91%
“…1:1) basis to insulin and, in addition to serving as a diagnostic tool for assessing pancreatic function in humans and domestic animals (for reviews see e.g. Leighton et al, 2017;Rosenfield et al, 2017), can be used as a proxy for nutritional status or energy balance (Emery Thompson, 2016). C-peptide is excreted at a consistent rate into urine and, in contrast to insulin, can be assessed from urine samples, enabling the repeated and non-invasive assessment of energetic condition (Emery Thompson, 2016), even in wild study populations.…”
Section: Introductionmentioning
confidence: 99%
“…Uji peptida C untuk diferensial diagnosis pada hewan terkena diabetes telah tersedia dalam dekade terakhir, meskipun masih terbatas beberapa spesies (Rosenfield et al 2017). Peptida C telah digunakan secara luas untuk mengukur fungsi sel beta pankreas.…”
Section: Peptida C Untuk Diagnosis Diabetes Pada Hewanunclassified
“…Tingkat penurunan konentrasi peptida C menggambarkan tingkat kerusakan pada sel beta pankreas (Ghorbani & Shafiee-Nick 2015). Rosenfield et al (2017) melaporkan bahwa peneliti telah berhasil membuat klon dan ekpresi gen pro-insulin pada anjing dan menggunakannya sebagai diagnosis standar untuk uji pro-insulin pada anjing. Protein hasil ekspresi tersebut dapat digunakan sebagai marker untuk mengidentifikasi disfungsi sel beta pada anjing.…”
Section: Peptida C Untuk Diagnosis Diabetes Pada Hewanunclassified